Battle of Britain [videorecording (DVD)] - Gething, Ashley; McGregor, Ewan, 1971-; McGregor, Colin (BFS Entertainment & Multimedia Ltd., 2011)
To mark the Battle of Britain's 70th anniversary, actor Ewan McGregor and his brother Colin, a former RAF pilot, take us on a journey to honor the heroes of 1940, bringing the amazing story of the Battle of Britain to a new generation. As Spitfires and Hurricanes once again fly over the White Cliffs of Dover, they reveal the inspiring personal stories of 'The Few' who were there and those still with us today.